,Furchtbare Passion‘ - Laura Beck (Recherches Germaniques)
This article deals with W.G. Sebald’s autobiographically tinged prose miniature Die Alpen im Meer (2001) and examines how its numerous descriptions of hunting and the killing of animals in general play into the overarching story of human destruction narrated in the text. The particular importance of the figure of the hunter is heightened and emphasized by the way Sebald incorporates intertextual references to Gustave Flaubert’s 1877 story La Légende de saint Julien l’Hospitalier into Die Alpen im Meer. In a comparative reading of both texts, this analysis aims to show how Sebald’s particular “use” of Flaubert’s conte (particularly the omissions and modifications) contributes to a (ultimately anthropocentric) representation of hunting/the killing of animals as a pivotal element in the history of human destruction.